INVESTIGATION OF INTERACTION BETWEEN SOME METAL SALTS CATIONS AND ACRILAMIDE BY IR-SPECTROSCOPY (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
IR-spectra of acrylamide are investigated at the presence of lithium and copper (Cu2+) chlorides, and also lithium perchlorate and nitrate in acetonitrile. It has been shown, that solvation of cations occurs due to their interaction both with oxygen of a carbonyl group, and with nitrogen of amide group. And this interaction substantially has donor-acceptor character.
Keywords: acrylamide; lithium and copper hlorides; ithium perchlorate and nitrate; acetonitrile; donor-acceptor character